2011
DOI: 10.4236/ijcm.2011.24062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weight Loss on Pericardial Fat and Left Ventricular Mass Assessed with Cardiac Magnetic Resonance Imaging in Morbid Obesity

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Following bariatric surgery, studies have reported conflicting results regarding LV end-diastolic volume, with increased ( 28 ), decreased ( 22 , 25 ) and no change being reported ( 26 , 27 ). This study shows a biphasic response of the LV cavity following weight loss, with the initially observed decrease in LV cavity size being followed by a longer-term increase in cavity size, back to the baseline size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following bariatric surgery, studies have reported conflicting results regarding LV end-diastolic volume, with increased ( 28 ), decreased ( 22 , 25 ) and no change being reported ( 26 , 27 ). This study shows a biphasic response of the LV cavity following weight loss, with the initially observed decrease in LV cavity size being followed by a longer-term increase in cavity size, back to the baseline size.…”
Section: Discussionmentioning
confidence: 99%
“…With the reduction in both subcutaneous (driving volume load and eccentric hypertrophy) and visceral adiposity (driving insulin resistance and concentric remodelling) following bariatric surgery, this would be expected. The results for left ventricular cavity size changes are far less consistent, with some reporting a reduction in LV cavity size ( 22 , 25 ) whilst others no change ( 26 , 27 ), or an increase ( 28 ). In this case, the early reduction in volume load that accompanies total fat mass reduction would be expected to reduce LV cavity size, however, the reversal of insulin resistance that accompanies bariatric surgery ( 29 ), may be expected over time to reduce concentric remodelling and thus increase LV cavity size.…”
Section: Introductionmentioning
confidence: 89%
“…The study by Snel et al 31 demonstrated that 16 weeks of very low calorie diet reduced body weight, PAT, AVAT, ASAT to 78, 83, 40, and 53% of baseline values, respectively. Schneiter et al 32 showed that BMI, EAT, and PAT + EAT were significantly reduced after gastric banding intervention. It is unknown whether exercise program and bariatric surgery have similar effects on the different visceral excessive fat deposits and their relative distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular diastolic dysfunction is congruent with long-lasting severe obesity and is associated with reduced eGFR [175]. Independently of a healthy or unhealthy status, the duration of severe obesity was a major risk of incident HF in the Nord-Excluding Schneiter et al [187], β Mean.…”
Section: Duration Of Obesity and Preserved Ejection Fraction Heart Fa...mentioning
confidence: 95%
“…Only a few studies examined the cardiac effects of MBS with CMR in patients with severe obesity. Eight adult studies comprising 170 subjects with severe obesity appraised LVM by CMR before and after MBS (Table 2) [181][182][183][184][185][186][187][188]. The mean reduction in LVM was 11.1% in these studies.…”
Section: Metabolic Bariatric Surgery and Left Ventricular Massmentioning
confidence: 99%